Salivary cortisol and alpha amylase enzyme levels in different phases of minor recurrent aphthous stomatitis - Mansour Ghada; Al-Johani Khalid; Safi Mohammad-Ayman (EDP Sciences, 2023)
Objectives: Recurrent aphthous stomatitis (RAS) is one of the most common oral mucosal lesions and stress is one of the major factors implicated in its causation. The aim of the present work is to measure the stress biomarkers, salivary cortisol (SC) and salivary alpha amylase (SAA), in the different phases of RAS. Patients and Methods: The study included 69 subjects of whom 38 patients served as the study group who suffered from minor RAS and one to three active minor oral ulcers of <48 h duration. The remaining 31 healthy subjects served as controls. Unstimulated salivary samples were collected twice from the study group; during the ulcerative phase of RAS and after complete healing has occurred, and only once from the controls. Concentrations of SC, and SAA enzyme were assessed by Enzyme-linked Immunosorbent Assay (ELISA). Results: There was a significant increase of SC and SAA in both the ulcerative and the post-healing phases in comparison to the control group. The ulcerative phase had higher but insignificant levels of both biomarkers when compared to the post-healing phase. There was a significant correlation between both biomarkers in the post-healing but not in the ulcerative phase. Conclusion: RAS patients have significantly higher levels of both stress biomarkers (SC and SAA) in the ulcerative and in the post-healing phases when compared to controls.